Diagnosing von Willebrand Disease: A Short History of Laboratory Milestones and Innovations, Plus Current Status, Challenges, and Solutions - Favaloro, Emmanuel J. (Seminars in Thrombosis and Hemostasis, 2014)
von Willebrand disease (VWD) is a disorder characterized by deficiency of, or defects in, von Willebrand factor (VWF). VWD was originally identified by Erik Adolf von Willebrand, who in early 1924 investigated a large family suffering from a bleeding disorder that seemed to differ from hemophilia. Erik von Willebrand undertook some initial laboratory investigations to conclude the involvement of a plasma factor, the lack of which prolonged the bleeding time, but failed to impair coagulation times and clot retraction. By the end of the 1960s, VWD was accepted as a combined deficiency of factor VIII (FVIII) and another plasma factor responsible for normal platelet adhesion. Just how these two functions were related to each other was less clear and the diagnostic tests available at the time were poorly reproducible, cumbersome, and unreliable; thus, VWD was poorly delineated from other coagulation and platelet disorders. The early 1970s saw a revolution in diagnostics when ristocetin was identified to induce platelet aggregation, and this formed the basis of the first consistent and reliable VWF “activity” test, permitting quantification of the platelet adhesive function missing in VWD. Concurrently, immunoprecipitating techniques specific for VWF were defined, and the application of such technologies permitted a clearer understanding of both VWF and VWD heterogeneity. Continued exploration of the structure and function of VWF contributed greatly to the understanding of platelet physiology, ligand receptor interaction and pathways of cellular interaction and activation. Recently, additional assays evaluating other functions of VWF, including collagen binding, platelet glycoprotein Ib binding, and FVIII binding, have improved the diagnosis of VWD. The purpose of this narrative review is to explore the history of phenotypic VWD diagnostics, with a focus on laboratory milestones from the past as well highlighting recent and ongoing innovations, and ongoing challenges and possible solutions.
Keywords: von Willebrand disease; diagnosis; von Willebrand factor; laboratory testing; ristocetin cofactor; collagen binding; VWF activity; history